Examining how cpec influences pakistan’s relationships with neighbouring countries and global powers - Dr. Muhammad Habib; Dr. Syeda Bushra Batool; Abdul Nafey Kakepota; Mahwish Naheed; Wajeeha Najam (Al-Qanṭara, 2025)
CPEC, which is dubbed as the ‘China-Pakistan Economic Corridor (CPEC)’, represents a centre point of China's Belt and Road Initiative (BRI). This project is boasted of being pivotal in terms of reshaping the geopolitical dynamics of South Asia and beyond. Since its commencement, CPEC has not only catalysed economic development in Pakistan but also significantly influenced Pakistan's diplomatic relations with neighbouring countries including India, Afghanistan, and Iran, as well as major global powers like China, the United States, and Russia. Considering these notions, this research endeavours to assess the geopolitical implications of CPEC by examining how it has strengthened Sino-Pakistani ties, escalated tensions with India, and altered Pakistan's diplomatic strategies on a global scale. Through an exhaustive literature review and thematic analysis of previous studies and geopolitical reports, this research attempts to explore the multifarious challenges and opportunities that CPEC poses and presents, respectively. The findings highlight the corridor’s potential in redefining regional alliances, drive economic integration, and shift power balances in South Asia, thereby, rendering key insights into the interconnectedness between economic initiatives and geopolitical strategies in the 21st century.